Retrofitting of damaged bridges – the sustainable solution. Issue 1 (27th May 2016) - Dissanayake, Ranjith; Bandara, Chaminda S.
ABSTRACT: Rehabilitation of damaged bridges may be more beneficial than building new bridges. However, proper methods are necessary to assess the level of damages and to verify the fitness of such bridges for further use. In the assessment, there are two important criteria to consider. One is the amount of damage due to fatigue caused by usual past vehicle loading and the other is the magnitude of damage caused by the unexpected actions. The present paper is about a wrought iron bridge damaged by floods. In order to do the assessment, a condition survey was first carried out. Then an analysis was done using a finite element model of the bridge. The model was validated using results of a field loading test. Both static and dynamic loading tests were conducted using a locomotive with six numbers of 13.16-ton axles for five different loading cases to measure the displacement, strain and acceleration at predetermined (critical) members of the bridge. Then the damage in the bridge due to past loading histories and the future fatigue life of the bridge were estimated. Furthermore, using the validated model, the ability of the bridge for higher loading situations was confirmed. The future life was found as 30 years with a factor of safety of 3. The cost estimated for retrofitting work and constructing new reinforced concrete abutments was much less than that for constructing a new bridge. Therefore, it was decided that the rehabilitation of the bridge with necessary retrofitting work is more economical and sustainable than demolishing it and constructing a new one. The bridge is now in use after being repaired, retrofitted and placed on new abutments.